Relaparotomy after caesarean section: an analysis of the risk factors, indications and outcome - Ahmed Khan, Naseema Beevi; Kolasseri, Smitha Sreenivas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Aim of this study was to establish the incidence of post caesarean laparotomy and identify the risk factors, indications and management. Methods: We conducted a retrospective observational study in a tertiary care hospital in North Kerala from January 1, 2011 to December 31, 2014 of the twenty seven cases which required relaparotomy following caesarean section. Results: In our study there were a total of 20928 caesarean deliveries and 27 cases required exploratory laparotomy following caesarean section. Majority of the cases were following emergency caesarean section, 23 cases (85.19%). The most common indication for the caesarean section was failure to progress in labour in 8 cases (29.63%). Relaparotomy was done within 24 hours after caesarean in 23 cases (85.19%). Regarding the indication of relaparotomy, 5 cases were due to atonic postpartum hemorrhage (18.52%) and 4 cases (14.81%) due to traumatic PPH. Intraperitoneal hemorrhage was seen in 12 cases (44.44%). Hysterectomy was required in a total of 21 cases (77.78%), of which 14 had total hysterectomy (66.67%). Third laparotomy following the relaparotomy was required in one case. Regarding postoperative complications, 8 cases (29.63%) required mechanical ventilation and 4 cases (14.81%) developed multiorgan failure. There were 5 cases of maternal death (18.52%). Conclusions: Decision to proceed for early reoperation after caesarean section is a real challenge. Indication of the primary surgery, patient’s preoperative condition and indication for relaparotomy will influence the outcome. Assuring meticulous hemostasis before closure is very important, as postpartum hemorrhage was the most common indication for relaparotomy. It is also important that relaparotomy should be done in centres with efficient blood transfusion facilities in order to reduce the morbidity and mortality.